Album of overtures - ROBERTS, Chas. J. (Carl Fischer, 1913)
Lustspiel OverturenThe midnight dreamnNormanSounds from the Sunny SouthnJolly FellowsnThe barber of SevillenJolly RobbersnItalians in AlgerianMasaniello